The Types of Directive Speech Acts Used In Minangkabaunese By FBS UNP Students - Putri, Cynthia Maharani; Jufrizal, Jufrizal (English Language and Literature, 2024)
This research aimed to analyze the types and types of directive speech acts that are most dominantly used by FBS UNP students, thereby providing valuable insight into the pragmatic aspects of their language use in certain situations. Understanding this type of directive speech act can have implications for language teaching and intercultural communication in the Minangkabau speaking community. This research was a types of qualitative research method. The researcher found (23,07%) data commands, (23,07%) data requests and (7,8%) data give permission were found. The type of directive speech act of suggestions is the most dominant used in (46,1%) data found.